Savings, Private Property and Sound Money: An Austrian Perspective on the Essential Pre-requisites to Economic Growth and Development - Chamberlin, Anton (2018)
The overarching goal of this paper is to provide an answer to the following question from the perspective of economists working within the Mengerian or Austrian tradition: What are the essential pre-requisites and pre-conditions for a process of economic growth and development to take place? In course of our discussion, we focus on three important pre-requisites. First, we look at the implications of the presence of time preference, especially for the importance that savings have for adopting longer and more productive production processes and boosting productivity. Second, we analyze the problem of economic calculation and isolate the important institutional pre-conditions that are necessary for the allocation of higher order goods: private property in higher order goods and the use of money. These institutional pre-conditions, as we discuss, are thus also essential for the process of economic growth. And finally, we discuss the importance of a sound monetary order for generating sustainable economic growth.